Accounting for Differences in Female Labor Force Participation between China and India - Mehtabul Azam; Luyi Han (Institute of Labor Economics (IZA), 2019)
Although, the male labor force participation rate is comparable in China and India, female labor force participation rate remains very low in India. In this paper, we examine the factors responsible for the difference in female labor force participation rate between the two countries by carrying out decomposition exercise at three points of time covering two decades. We find that the differences in female labor force participation rate are not explained by the differences in characteristics across the two countries in each of the three year studied. The differences in returns to these characteristics explain most of the differences in participation rate.
Keywords: J16; J82; 330; female labor force; China; India; oaxaca-blinder decomposition